2015
DOI: 10.15835/buasvmcn-vm:10568
|View full text |Cite
|
Sign up to set email alerts
|

Compositional Studies on Mangalitsa Meat Products for Public Consumption

Abstract: Mangalitsa pigs are beginning to receive once again the public and media attention given the particular nutritive aspects compared to other types of breeds. The aim of our study was to assess the biochemical composition of Mangalitsa meat, related to various anatomical regions of the carcass. The main parameters that were taken into study were represented by: protein, water, collagen, fat, fatty acids and cholesterol levels. The material was represented by 10 Mangalitsa pigs, Blod variety, raised in a traditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…SFAs are also important in Mangalitza fat, especially palmitic, stearic, and myristic acids. However, their relative concentrations differ with the variety, rearing conditions, feeding, and processing [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…SFAs are also important in Mangalitza fat, especially palmitic, stearic, and myristic acids. However, their relative concentrations differ with the variety, rearing conditions, feeding, and processing [ 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Mangalitsa meat and fat do not contain a lower level of cholesterol than other breeds of pigs. The cholesterol is the natural component of each cell, being the base for vitamin D synthesis and steroid hormones (Cordis et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the fatty acids profile, we revealed that Bazna pork meat has a high value, having a slightly higher levels of polyunsaturated fatty acids than that shown by a previous study on Mangalitsa pork meat (Cordiş et al,2015). The results obtained are shown in Table 2.…”
Section: Figure 2 the Variation Of Fat And Protein According To Carca...mentioning
confidence: 59%